ВОЗРАСТНЫЕ ОСОБЕННОСТИ ИНТОНАЦИИ В РЕЧИ ЖИТЕЛЕЙ УЭЛЬСА - Карпова, Дар'я Михайлівна (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2015)
The investigation is devoted to the analysis of Wales inhabitants' intonational age peculiarities in speech. Тhе interest to the problem of intonational variation of English in Wales is conditioned Ьу the study of interfering influence of the Welsh language in the speech of bylinguists. The investigation conducted on authentic speech of the Welsh with the account of age factor allows to conclude that specific intonational model - rising-falling terminal tone (RFТ) which exists in the situation of diglossia and is conditioned Ьу coпelation ofEnglish and Welsh intonational elements is socially differentiated.